PENGEMBANGAN SISTEM MANAJEMEN POLA MAKAN NOGER BERBASIS WEB DAN ANDROID UNTUK PENDERITA GERD - Nurhaliza Aufa Salwa; Sri Wulandari (LPPM Universitas Abdurrab, 2025)
Gastroesophageal Reflux Disease or GERD is a disorder that causes gastric acid secretion to increase into the esophagus. One of the risk factors that potentially can worsen GERD is the unhealthy consumption habit. In fast-paced environment, GERD sufferers often ignore meal schedules for many reasons, either its because focusing on professional responsibilities, academic assignment, or digital activities such as gaming. This study aims to develop a meal schedule management system for gastric acid patients as an effort to suppress GERD symptoms. This study uses the Waterfall approach as a methodological framework. Noger system is designed to provide a reminder system and menu guidance in managing meal schedules for people with gastroesophageal reflux disease. The benefits of Noger for users are to provide convenience for GERD sufferers in planning healthy consumption schedules and menus. The research findings revealed that Noger showed good performance, with blackbox evaluations proving success according to the initial design. By adopting a structured approach to consumption habits, clinical symptoms of maag linked to irregular eating routines can be effectively managed. The system aims to enhance the quality of life by focusing on meal planning and scheduling, offering a digital health solution tailored for individuals with gastric acid disorders.